SISTEM INFORMASI PELAYANAN KEPENDUDUKAN KELURAHAN CIJANTUNG - Ardi Putro Prakoso, - (2019)
With the development of technology and science during this period of globalization is felt increasingly rapid and sophisticated and systems used by humans. For companies or government agencies that want to progress, having information that is faster, more accurate, and timely is needed. The aim of the study was to design and build a Population Services Information System in Cijantung Village to improve the quality of services for outreach officers and the use of services for outpatients. The benefits obtained from this study are that this system can facilitate urban village officials in serving residents or residents in requests for letters and data storage dynamically. This study uses the PIECES method and the waterfall mode as the basis for reference in making the system. The conclusions of the research results are that the Population Services Information System can facilitate the population service activities at the village level, with notes, holding training or direction and holding facilities that support its implementation